Conflict appraisals as a mediator of the association between marital conflict and rumination in adolescents - Melia, Nathan Lincoln, author; Lucas-Thompson, Rachel G., advisor; Coatsworth, Doug, committee member; Gingerich, Karla, committee member (Colorado State University. Libraries, 2015)
A large number of studies have demonstrated that exposure to marital conflict negatively impacts children. Rumination is a cognitive process of children to such exposure that has been found to lead to both internalizing and externalizing behaviors, and may be linked to exposure to marital conflict. In this thesis, I examined whether marital conflict is related to rumination, and whether this association is mediated by adolescent conflict appraisals of marital conflict. One hundred and fifty-three adolescents (ages 11-17) reported on conflict appraisals surrounding marital conflict and cognitive coping strategies. Marital conflict was assessed via parent-report with a partnership questionnaire measuring intensity, frequency, and hostility of parental conflict. Results indicated that marital conflict was related to greater rumination about negative events.